End-User Adoption of Bitcoin in South Africa - Jankeeparsad, Raphael Warren; Tewari, Dev (Journal of Economics and Behavioral Studies, 2018)
Since its introduction in 2008, the value and popularity of Bitcoin have risen exponentially. Despite being 10 years old, the concept of crypto currency is fairly new in South Africa. The increase in the value of Bitcoin, together with extensive media coverage, has led to the creation of a Bitcoin economic system with many South Africans jumping on the Bitcoin bandwagon. This study aims to identify the determinants affecting end-user adoption of Bitcoin in South Africa and to determine the main use of the crypto currency by South Africans. A research model was developed utilising constructs from the technology acceptance model and theory of planned behaviour. The model was then tested empirically by utilising two survey-based questionnaires, one for current users of Bitcoin and one for non-users. For users, perceived usefulness and access to facilitating conditions were the primary determinants influencing their decision to adopt the crypto currency while lack of trust and social influences were the primary reasons non-users chose not to adopt Bitcoin.